Investigation of carbonate addition on essential element concentrations in various teas - Yalcin, Tugce; Uygunoz, Deniz; Kipcak, Azmi Seyhun; Derun, Emek Moroydor (YILDIZ TECHNICAL UNIV, 2024)
Daily consumption of various teas is a popular tradition in many countries especially in Turkey and although it shouldn't be in tea, carbonate can be added to obtain more brew from teas especially in local coffeehouses. In this study, the effect of carbonate addition on the essential element concentrations of some black teas (black, earl grey and green tea), herbal teas (fennel, mint and sage tea) and fruit teas (apple, lemon and rosehip) is analysed by inductively coupled plasma optical emission spectrometer (ICP-OES), after the infusion process of tea brewing with carbonate. Afterwards, the total element contents of the tea grains in are determined by again ICP-OES prior to microwave digestion process. Considering the data obtained from the experiments, carbonate addition increased or decreased some elements with respect to the tea types. According to the results obtained after the microwave digestion method, although the major elements in all types of teas are found as Ca, K, P, Mg and Mn, which do not reach 2% brewing from the tea grains, carbonated infusion is not recommended due to its increasing effect on the concentration of the major elements contained in teas.
Keywords: Black Tea; Carbonate Effect; Element; Fruit Tea; Herbal Tea; TRACE-ELEMENTS; LEMON; INFUSIONS; Engineering